Multi-Agent Modeling of Project Management Processes in Distributed Teams - Cherednichenko, O. Yu.; Matveiev, O. M.; Yanholenko, O.; Maneva, R.; Матвєєв, О. М.; Чередніченко, О. Ю. (CEUR Workshop Proceedings, 2021)
Changes in the business environment, the innovative nature of projects, lack of necessary skills of project team members lead to increased uncertainty and inability to plan with a given degree of accuracy. Such projects use adaptive project and program management methodologies. In the field of information technology,the use of multi-agent systems is of particular interest. In the context of the use of multi-agent systems for the design of intelligent systems for various purposes, the development and study of a model and software implementation of a prototype of an agent platform are relevant. The aim of this work is to develop and research an agent platform that can be implemented in the work of the distributed team in order to improvetheassignment of tasks. The paper presents the formal agent architecture as a basis of multi-agent model. The task assignment is a case studyto implement and test multi-agent model prototype. The agent platform is developed based on Kotlin programming language. A prototype of the agent platform based on the FIPA specification allows to increase the productivity, scalability and interoperability of multi-agent system.
Keywords: Project management; distributed team; task assignment; multi-agent platform; formal agent architecture; prototype